Ultrastructures of porostromate microproblematica from a Mulde Event (Homerian, Silurian) Bioherm in Podolia, Western Ukraine - Castagner, Ariane; Jarochowska, Emilia; Munnecke, Axel; Desrochers, André (Estonian Journal of Earth Sciences, 2015)
The Mulde Event (Homerian, Wenlock) of the Silurian is characterized by a positive δ13C isotope excursion, a stepwise extinction of the hemipelagic fauna and an increase in non-skeletal deposits thought to be microbial, proliferating in shallow marine environments. There is little known about whether the proliferation of microbialites is due to reduced grazing, increased seawater saturation state or an increase in nutrient supply. We have studied a Mulde Event-associated buildup from the Muksha Formation in Bagovytsya, Podolia, Western Ukraine. This buildup differs from a typical Silurian skeletal reef in its low abundance of rugose and favositid corals. The framework of this reef is dominated by stromatoporoids, heliolitid corals and calcimicrobes, the last ones encrusting the stromatoporoids and shells and also forming oncoids. Several microproblematica are present, including Girvanella, Rothpletzella and Hedstroemia, along with Ortonella-like porostromate problematica. This study attempts to further identify the Ortonella-like porostromate problematica and Hedstroemia through SEM analyses which have revealed a recrystallized structure with microdolomite, indicating an originally high-Mg calcite composition. This suggests a red algal affinity or possibly a microbial origin. Our observations may help to constrain the environmental controls on the development of microbial- and microproblematica-dominated deposits during the Mulde Event.
UnivIS-Import:2015-04-14:Pub.2015.nat.dgeo.IGM.LP.ultras
Keywords: Calcimicrobes; Carbon isotope excursion; Hedstroemia; Microbialite; Reefs; Silurian